(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Whole Body Radioiodine Scan with 131I is an important investigation in the management of patients with differentiated thyroid carcinomas. However, it is also useful in the evaluation of ectopic thyroid tissues and congenital thyroid abnormalities. Reported case of a 50-year-old hyperthyroid woman with history of thyroidectomy for toxic multinodular goiter had no malignancy histopathologically, but without Levothyroxine replacement therapy, she was found to be subclinical hyperthyroid biochemically. Whole body radioiodine scan with 131I showed a focus of intense radiotracer concentration below the sternum and indicated that the patient had resto-sternal goiter which was undiagnosed. CT scan of the lower neck and upper chest confirmed the diagnosis as well. Bangladesh J. Nuclear Med. 27(2): 290-292, 2024